Higher hospital referral concentration associated with lower‐risk patients in skilled nursing facilities. (29th March 2021) - McHugh, John P.; Rapp, Thomas; Mor, Vincent; Rahman, Momotazur
Abstract: Objective: To examine whether stronger referral relationships between hospitals and skilled nursing facilities (SNF) are associated with lower‐risk patients being admitted to SNF. Data Sources/Collection: We used MedPAR data to estimate referral relationship strength and nursing home survey data (OSCAR and CASPER) to determine the risk of patient admissions at nearly 14 000 SNFs from 2008 to 2014. Study Design: We examined the association of hospital referral concentration with the percentage of higher‐risk patients admitted to non‐hospital‐based (freestanding) SNFs using an instrumental variables approach. We used the distance between patients and SNFs and hospitals and SNFs as the instrument. Data Collection/Extraction Methods: We used previously collected MedPAR and OSCAR/CASPER survey data. Principal Findings: We find greater observed referral concentration among freestanding SNFs is associated with lower percentages of patients with pressure sores (coefficient, −2.64; 95% CI, [−2.82 to −2.46]), catheters (−0.55; [−0.74 to −0.36]), and physical restraints (−0.16; [−0.29 to −0.03]) at admission to a skilled nursing facility. Conclusions: We find evidence that freestanding SNFs with stronger hospital referral relationships may be admitting less risky patients, possibly contributing to disparities across SNFs.